PROBLEMS OF BILINGUALISM AND ITS EFFECTS ON THE LANGUAGE PERSONALITY - Buranova, Dildora (Журнал иностранных языков и лингвистики, 2021)
The paper will discuss these two views further regarding three main dimensions. They are as follows: bilingualism and intelligence, bilingualism and education, and bilingualism and personality. Then I will try to explain why the two views are so contradictory